Berita Kriminalitas di Kalimantan Dalam Koran Bintang Borneo Analisis Bulan Februari 1929 - Nadira Athailla; Michael Silvester Mitchel Vinco (Amarthapura: Historical Studies Journal, 2023)
News about criminal acts published in newspapers or the Bintang Borneo Newspaper which focuses on the year 1929 from february to find out the content of the news and how many times the criminal acts occurred. This research uses a descriptive qualitative method with the approach used in analyzing namely using a historical analysis approach. Historycal analysis is an analysis that aims to reconstruct events that occurred in the past objectively and systematically. The primary source for this research uses archives from newspapers or newspapers, while secondary sources are obtained from books, jurnals, and websites that contain explanations about crime. After analysis, crime news in the Bintang Borneo newspaper occurred four times in a period of one months (february). The forms of criminal acts range from theft, robbery, fights, assault, to murder